Financing Attitude of Islamic and Conventional Banking Institutions towards Small and Medium-Sized Enterprises (SMEs) in Pakistan - Sharif, Saqib; Baig, Mirza Abdul Mateen (Islamic Banking and Finance Review, 2023)
Purpose: The current study attempted to investigate the banks’ financing attitude towards Small and Medium-Sized Enterprises (SMEs) in Pakistan. The study further aimed to determine the difference in financing attitude between Islamic and conventional banks. Design/Methodology/Approach: The quarterly data was collected from the State Bank of Pakistan’s (SBP’s) website (the Central Bank of Pakistan). Moreover, regression analysis was applied to contrast the attitude of Islamic and conventional banking institutions in Pakistan towards SMEs financing. Findings: The evidence suggested that Islamic banking institutions are more inclined towards financing SMEs as compared to their conventional counterparts. However, overall, the results were weakly significant at 10% level. Research Limitations/Implications: The current study examined the attitude of the type of banks towards SME financing and compared Islamic financial institutions with conventional ones. However, SMEs outstanding financing data by individual financial institutions was not available, which could, if available, help to understand lending attitudes at a bank level. Originality/Value: To the best of authors’ knowledge, no study has discussed and compared financing attitudes of Islamic and conventional banking institutions towards SMEs in Pakistan so far. Therefore, the current study attempted to fill this gap by contributing to the extant literature on financing to SMEs. Moreover it also added new dimensions and as per the authors’ knowledge, it was the first research conducted on banking-type level in Pakistani context.